Integration of Artificial Intelligence by Tertiary Education Students in Zimbabwe: A Case of Responsibility and Accountability in Academic Writing - Mukwerete, Kwanisai; Matiza, Namatirai Chikusvura (Randwick International of Education and Linguistics Science Journal, 2025)
This study examined how students utilise various AI tools responsibly and accountably in their academic writing. The study adopted a qualitative approach with data collected using an electronic questionnaire from self-selected participants. The questionnaire was uploaded to Google Forms, and a total of twenty-five participants took part in the study until data saturation was reached. Atlas. ti was utilised for data analysis due to its robust analytical capabilities. The findings highlighted the importance of responsible and accountable use of AI tools, as these practices enhance students' intellectual capabilities and foster innovation. The findings also indicate that use of AI tools play a crucial role in the lives of tertiary education students by enhancing the quality of their academic writing. It improves grammar, structure, and coherence, making the content more readable. Additionally, the study uncovered several challenges that students face regarding the use of AI in education. The study provided recommendations on best practices for employing AI in academic writing for tertiary-level students in Zimbabwe. Additionally, it advocated for all tertiary institutions to invest in plagiarism detection software(s) to ensure that the use of AI tools is accompanied by accountability in all written coursework, thereby contributing to students' final degree classifications.